Thermonucleases Contribute to Staphylococcus aureus Biofilm Formation in Implant-Associated Infections–A Redundant and Complementary Story - Yu, Jinlong; Jiang, Feng; Zhang, Feiyang; Hamushan, Musha; Du, Jiafei; Mao, Yanjie; Wang, Qiaojie; Han, Pei; Tang, Jin; Shen, Hao (Frontiers in Microbiology, 2021)
Biofilms formed by Staphylococcus aureus are one of the predominant causes of implant-associated infections (IAIs). Previous studies have found that S. aureus nucleases nuc1 and nuc2 modulate biofilm formation. In this study, we found low nuc1/nuc2 expression and high biofilm-forming ability in IAI isolates. Furthermore, in a mouse model of exogenous IAIs, Δnuc1/2 exhibited higher bacterial load on the surface of the implant than that exhibited by the other groups (WT, Δnuc1, and Δnuc2). Survival analysis of the hematogenous IAI mouse model indicated that nuc1 is a virulence factor related to mortality. We then detected the influence of nuc1 and nuc2 on biofilm formation and immune evasion in vitro. Observation of in vitro biofilm structures with scanning electron microscopy and evaluation of bacterial aggregation with flow cytometry revealed that both nuc1 and nuc2 are involved in biofilm structure and bacterial aggregation. Unlike nuc1, which is reported to participate in immune evasion, nuc2 cannot degrade neutrophil extracellular traps. Moreover, we found that nuc1/nuc2 transcription is negatively correlated during S. aureus growth, and a possible complementary relationship has been proposed. In conclusion, nuc1/nuc2 are complementary genes involved in biofilm formation in exogenous IAIs. However, nuc2 contributes less to virulence and is not involved in immune evasion.